The Complete Chloroplast Genome of Plukenetia volubilis Provides Insights Into the Organelle Inheritance - Villanueva-Corrales, Simón; García-Botero, Camilo; Garcés-Cardona, Froilán; Ramírez-Ríos, Viviana; Villanueva-Mejía, Diego F.; Álvarez, Javier C. (Frontiers in Plant Science, 2021)
Plukenetia volubilis L. (Malpighiales: Euphorbiaceae), also known as Sacha inchi, is considered a promissory crop because of its high seed content of unsaturated fatty acids (UFAs), all of them highly valuable for food and cosmetic industries, but the genetics basis of oil biosynthesis of this non-model plant is still insufficient. Here, we sequenced the total DNA of Sacha inchi by using Illumina and Nanopore technologies and approached a de-novo reconstruction of the whole nucleotide sequence and the organization of its 164,111 bp length of the chloroplast genome, displaying two copies of an inverted repeat sequence (IRA and IRB) of 28,209 bp, each one separating an SSC region of 17,860 bp and an LSC region of 89,833 bp. We detected two large inversions on the chloroplast genome that were not presented in the previously reported sequence and studied a promissory cpDNA marker, useful in phylogenetic approaches. This chloroplast DNA marker was used on a set of five distinct Colombian cultivars of P. volubilis from different geographical locations to know their phylogenetic relationships. Thus, we evaluated if it has enough resolution to genotype cultivars, intending to crossbreed parents and also to follow this marker in the F1 generation. We finally elucidated, by using molecular and cytological methods on cut flower buds, that the inheritance mode of P. volubilis organellar DNA is maternally transmitted. This de-novo chloroplast genome will provide a valuable resource for studying this promissory crop, allowing the determination of the organellar inheritance mechanism of some critical phenotypic traits and enabling the use of genetic engineering in breeding programs to develop new varieties.